Comparative Study of Steel, Bamboo and Glass Fiber as reinforcing material in Concrete Beams - Kumar, Anand; Supe, Jayant (International Journal of Scientific Research in Civil Engineering, 2020)
Concrete is the most principally utilized material in the development field took after by steel as reinforcements. The present day situation is seeing a quick change in the building material industry and step by step new innovations are supplanting the ordinarily utilized materials. Scientists everywhere throughout the world are endeavoring to enhance concrete by the utilization of fibers, pozzolanas and different admixtures. Steel is given in the pressure side fundamentally in order to balance the powerless zone of concrete that is Tension. In spite of the fact that it is thought to be the best for this work yet at the same time it gets eroded by the activity of the nature in this way, emerges the point of searching for an option. A standout amongst the most well-known choices is Fiber strengthened polymer rebars (FRP’s). In the present trial examination supplanting of Ordinary Concrete with Glass fiber and bamboo fiber Reinforced Concrete along these lines considered on the progressions of Compressive Strength and Ultimate Crushing loads. This study comparatively evaluated the flexural performance and deformation characteristics of concrete elements reinforced with bamboo (Bambusa vulgaris), Glass fiber and the twisted steel rebars. The yield strength (YS), ultimate tensile strength (UTS) and the elongation of 9 specimens of the three materials were determined using a universal testing machine. These beams of concrete strength 25 N/mm2 at age 7, 14 and 28 days were separately reinforced with bamboo, glass fiber and steel bars of same percentage, while the stirrups were essentially mild steel bars. It is Determined that out of three which material sample is suitable rebars for non-load bearing and lightweight RC flexural structures also bonding and load-carrying capacity.